DESAIN SISTEM INFORMASI SURVEILANS PEMETAAN PASIEN PENDERITA HIV/AIDS ORIENTASI OBJEK DENGAN UML (Studi Kasus : Klinik Mawar RSUD Indramayu ) - Mukhfid, Mukhfid; Darsanto, Darsanto; Juniarti, Tri Intan (Department of Computer Engineering, Universitas Wiralodra, 2024)
The Mapping Surveillance Information System for HIV Patients is a system designed to collect, store, manage and analyze data related to patients suffering from HIV and the location of the spread of the disease. The concept itself combines information technology with data on HIV patients and geographic location data to produce a better understanding of the spread of HIV disease and to optimize patient care and management. The lack of availability of an information system to utilize the technology available at the Mawar Clinic, Indramayu District Hospital in recording, processing data and reporting HIV/AIDS surveillance activities has resulted in duplication of data and ultimately resulted in the resulting output not providing an accurate picture of the HIV epidemic situation. The research that the author conducted was descriptive in nature by carrying out several information system developments which were created using the system development life cycle method or SDLC (System Development Live Cycle) through the Waterfall model which has 5 (five) stages, namely Requirements Analysis, System Design, Implementation, System Testing , and Maintenance. To design the system, use the Object methodology with UML (Unified Modeling Language), including use case diagrams, activity diagrams, sequence diagrams and class diagrams. The final result of this research is a software/information system that helps related parties in making decisions regarding the handling and treatment of HIV/AIDS patients in Indramayu quickly and accurately.